A coupled smoothed particle hydrodynamic and finite particle method: An efficient approach for fluid-solid interaction problems involving free-surface flow and solid failure. (September 2020) - Liu, Feihong; Yu, Ying; Wang, Qinhua; Luo, Yaozhi
Abstract: In this paper, an efficient numeric approach coupling smoothed particle hydrodynamics (SPH) with finite particle method (FPM) for fluid-solid interaction (FSI) problems is proposed and discussed. SPH is used for modeling fluid domains because of its ability to simulate free-surface flow. FPM is used to model solid domains as discretized particles to address motion, deformation, fracture and contact. The treatments of reduction of rigid body motion in FPM achieve a high efficiency for very large deformation analysis. The coupled SPH with FPM has been developed for imposing boundary condition by employing virtual particles. The proposed scheme is validated by published benchmark examples, and the results demonstrates good agreement with experimental, numerical and analytical results. The results of simulation of FSI problems with solid failure also indicates that the coupled SPH and FPM is straightforward in concept, and efficient in modeling solid failure and FSI with free-surface flow, which is promising for addressing nonlinear, fracture and contact problems in FSI processes.